2006
DOI: 10.1142/s0219887806001843
|View full text |Cite
|
Sign up to set email alerts
|

Gauge-Natural Parametrized Variational Problems, Vakonomic Field Theories and Relativistic Hydrodynamics of a Charged Fluid

Abstract: Variational principles for field theories where variations of fields are restricted along a parametrization are considered. In particular, gauge-natural parametrized variational problems are defined as those in which both the Lagrangian and the parametrization are gauge covariant and some further conditions is satisfied in order to formulate a Nöther theorem that links horizontal and gauge symmetries to the relative conservation laws (generalizing what Fernández, García and Rodrigo did in some recent papers). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…In [BFF07] we have shown that the coefficients E A , F µ A and F µν A are the components of two global morphisms…”
Section: Definition 15mentioning
confidence: 99%
See 2 more Smart Citations
“…In [BFF07] we have shown that the coefficients E A , F µ A and F µν A are the components of two global morphisms…”
Section: Definition 15mentioning
confidence: 99%
“…In particular we find that the non-holonomic theory seems to be non physical (every admissible section is a solution). Let us consider a region M of spacetime with metric g αβ (here we consider it to be fixed, but if we want to study the coupling with gravity the formalism can do it as well, see [BFF07]) filled with a barotropic and isoentropic fluid. The world lines of the fluid particles and its density describe completely the configuration of the system.…”
Section: Relativistic Hydrodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us review here a variational formulation of relativistic hydrodynamics that was originally presented in detail in Ref. [5]. It is in practice equivalent to the ones of Refs.…”
Section: The Variational Framework For Relativistic Hydrodynamicsmentioning
confidence: 99%
“…Here, (y (i) ,ẏ (i) ) is a coordinate system on the ith factor of T S N . Note that there is no summation over the index i in (1), and that the summation over individual coordinates is implicit, as shown in the term between brackets.…”
Section: Modeling the Constraint Forcesmentioning
confidence: 99%